Lattice Ordered Neutrosophic Soft Set and Its Usage for a Large-Scale Company in Adopting Best NGO to Deliver Funds During COVID-19 - Vimala, J.; Rajareega, S.; Preethi, D.; Al-Tahan, M.; Mahalakshmi, P.; Jeevitha, K.; Ashma Banu, K. (Journal of Computational and Cognitive Engineering, 2022)
Soft sets, fuzzy sets, lattices, and their generalisations have always been significant for research on uncertainties. By combining the parameterization tool and neutrosophic logic, neutrosopic soft sets are developed to overcome uncertainty in terms of falsity, indeterminancy and truth membership vaules. In this study, we generalised the concept of lattice(anti-lattice) ordered neutrosophic soft set and some results are demonstrated by using restricted union, restricted intersection, extended union, and extended intersection. Using this theory, an application is developed to assist decision makers in selecting an NGO to use the Covid-19 fund of a large scale company where some order exists among the elements of parameter sets. Received: 23 March 2022 | Revised: 20 April 2022 | Accepted: 7 June 2022 Conflicts of Interest The authors declare that they have no conflicts of interest to this work.